English Discontinuous Structures (Journal of the College of Basic Education, 2023)
This paper examines the possibility of inserting linguistic elementsin unusual positions. The outcome of such insertion has come to beknown as a discontinuous structure. Learners of English as a foreignlanguage are warned against the use of such structures in their speech orwriting. However, in several cases the insertion of a word or a clausewithin a constituent or between constituents becomes obligatory orstylistically preferable. One striking example is the use of adverbialsbetween the main verb of a sentence and its direct object when the objectof the sentence is long or heavy.